Short-Term Surgical Outcomes for Lobectomy Between Robot-Assisted Thoracic Surgery and Uniportal Video-Assisted Thoracoscopic Surgery - Zhang, Fan; Xu, Lin; Lu, Hongda; Ma, Anqun; Wang, Gongchao (Frontiers in Oncology, 2022)
Abstract Objectives: To evaluate the short-term outcomes of uniportal video-assisted thoracoscopic surgery (UVATS) and Da Vinci robot-assisted thoracoscopic surgery (RATS) in lobectomy and lymph node (LN) dissection. Methods: The two groups of patients with primary non-small cell lung cancer (RATS group, UVATS group) were matched by propensity score to compare lymph node dissection and recent clinical outcomes. The results were analyzed by univariate analysis. From November 2020 to November 2021, 412 NSCLC patients (54 RATS and 358 UVATS) from a single institution of the Provincial Hospital affiliated with Shandong First Medical University were included in the analysis. Age, sex, lung lobe, surgical resection scope, solid nodules, and core tumour ratios (CTR) were matched according to different surgical methods.Results: From November 2020 to November 2021, 412 patients with non-small cell lung cancer (54 RATS, 358 UVATS) from the Provincial Hospital affiliated with Shandong First Medical University were included in the analysis. According to our matching results, lymph node dissection was more thorough in the RATS group.Conclusion: Robot-assisted thoracoscopic surgery has potential advantages over video-assisted thoracoscopic surgery in radical lung cancer surgery.